2022
DOI: 10.25295/fsecon.1040173
|View full text |Cite
|
Sign up to set email alerts
|

Rational Drug Use: An Applicatıon in Ankara Universıty Faculty of Health Sciences

Abstract: Drugs are an integral part of the health system, and our health. Rational drug use improves the quality of life and contributes the better health of society. Irrational use of drugs has a significant share in health spending. This study has been conducted to determine the approaches of Ankara University Faculty of Health Sciences' students about rational drug use. 2842 students studying in six departments in Ankara University Faculty of Health Sciences in the 2017-2018 academic years constitutes the universe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…82.3% of the 1stgrade students, 88.1% of the 2nd-grade students, 72.9% of the 3rd-grade students, and 92.3% of the 4th-grade students have responded "the doctor." In the study of Kuyifatih and Karakurt et al, similar to the results of this study, it was shown that a high percentage of students rely on doctors as a source to obtain the drug and read the instructions about the drug 21,24 . These results show that young people have positive attitudes towards drug use.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…82.3% of the 1stgrade students, 88.1% of the 2nd-grade students, 72.9% of the 3rd-grade students, and 92.3% of the 4th-grade students have responded "the doctor." In the study of Kuyifatih and Karakurt et al, similar to the results of this study, it was shown that a high percentage of students rely on doctors as a source to obtain the drug and read the instructions about the drug 21,24 . These results show that young people have positive attitudes towards drug use.…”
Section: Discussionsupporting
confidence: 80%
“…20 In the study by Kuyifatih et al at Ankara University, 60.2% of the participants stated that they use unprescribed medicine and the most common use of unprescribed medicine is with the percentage 52.1% painkillers. 21 While this study is evaluated with the other studies, the conclusion is that participants do consult a doctor while they're ill but partially behave through their previous experiences. Especially younger age groups tend to behave this way more than the other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…17 In another study of 2842 students in a Health Sciences Faculty, 52.1% of the students stated that they used painkillers without a prescription, and the percentage of students with a high income level using painkillers was lower than that of other income groups. 18 Although the rational drug use points of the current study patients who used drugs regularly were high, the scores were determined to be below the RDUS cutoff value of 35 points. Patients who used painkillers only when they were in pain were found to have lower RDUS points, which was thought to be due to conscious behavior to relieve the negative condition created by pain and focus on the outcome of pain relief.…”
Section: Discussionmentioning
confidence: 82%